2008
DOI: 10.1097/ta.0b013e31817c50d4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Decompressive Craniectomy for the Treatment of Severe Traumatic Brain Injury

Abstract: The majority of survivors after decompressive craniectomy have a good functional outcome as analyzed by GOSE. Overall, 30% of patients with STBI who underwent decompressive craniectomy had a favorable long-term outcome. Improving patient selection and optimizing timing of this procedure may further improve outcome in these very severely brain injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 15 publications
4
75
1
Order By: Relevance
“…[11] Better outcomes of patients after TBI is ensured by early intubation [12,13] and surgery. [1,14] Recovery of neurological patients is usually long, and TBI patients can gradually improve even after several months. [15] Early intensive rehabilitation may improve the functional outcome of patients with TBI in the early months after injury and hence increase the chance of their returning to work early.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Better outcomes of patients after TBI is ensured by early intubation [12,13] and surgery. [1,14] Recovery of neurological patients is usually long, and TBI patients can gradually improve even after several months. [15] Early intensive rehabilitation may improve the functional outcome of patients with TBI in the early months after injury and hence increase the chance of their returning to work early.…”
Section: Resultsmentioning
confidence: 99%
“…The favorable effect of surgery was also demonstrated in other studies. [14] If we follow the right branch of the classification tree, we can see that the second most important factor for better outcome after severe TBI was pCO 2 ; a level higher than 34 mmHg improved the GOSE score by two points (Node 5: 3.2±2.1 vs. Node 6: 5.2±1.9). This is not unexpected because higher pCO2 is an indicator of a better cardiac output and hence better brain blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of surgical treatment for traumatic head injuries depends on the preoperative condition of the patient (11,13,23). Recently, a number of surgical biomarkers for TBI patients have been proposed, and these are mainly based on ICP, CPP and imaging data (3,7,19,30).…”
Section: Discussionmentioning
confidence: 99%
“…1). However, the pertinent literature demonstrates a wide variation in clinical outcomes, and ill-defined indications for performing DC in patients with S-TBIs [Aarabi et al, 2006;Howard et al, 2008;Jagannathan, et al, 2007;Morgalla et al, 2008;Münch et al, 2000].…”
Section: Decompressive Craniectomy: Historical Landmarksmentioning
confidence: 99%
“…Does the performance of DC provide better functional outcome? Several clinical studies have suggested that DC reduces ICP but the overall functional outcome remains essentially unchanged [Danish, et al, 2009;Howard, et al, 2008;Morgalla, et al, 2008]. During the last decade a systematic attempt was made to prospectively assess the role of DC in the management of patients suffering S-TBIs and/or presenting medically refractory intracranial hypertension [Ban, et al, 2010;Morgalla et al, 2008;Valadka & Robertson, 2007].Two independent, parallel, multi-centric, prospective clinical studies (the DECRA and the Rescue ICP trials) were designed and are underway for evaluating the exact role of DC in the management of patients with S-TBIs.…”
mentioning
confidence: 99%